Pola Interaksi Sosial Anak dan Guru, Modal Pengetahuan dan Sosial dalam Meningkatkan Kecerdasan Emosional Sosial - Muhammad Ja'far Shodiq; Subaidi Qomar (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2022)
This study aims to identify and determine patterns of social interaction in improving children's emotional intelligence. As homosocious, humans cannot be separated from interaction activities. The diversity of each person in the surrounding environment gives rise to patterns of social interaction. This study uses a qualitative research method design with a case study approach with 4 sources through data collection techniques in the form of observation, interviews, and documentation. Researchers get the results that the pattern of social interaction that occurs at the TPA Masjid Al-Ikhlash Tempel Sleman is an associative type of social interaction pattern. The interactions built by students tend to stand out in the components of cooperation and accommodation which are characterized by mutual cooperation, helping, and being a mediator when other students fight. Meanwhile, this associative interaction pattern is categorized as quite capable in increasing the emotional intelligence of students. This is because some students have not been able to control their emotions well so that they cross the line, the majority of students have a sense of sensitivity to others both peers and across ages (empathy), and some students have high social skills and motivation so they tend to be less productive and effective in doing anything.